Lake George and Lake Champlain Paper - The Wheeler Process for Welding Iron and Steel without the Use of Fluxes - D. Torrey (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1879)
Considering the two great interests of to-day, in iron upon the one hand and steel upon the other, and recognizing with measurable distinctness the peculiar fitness of each for special services to which they are applied, the proposition to unite the two metals in combination, to bring into simultaneous use the peculiar advantages which each offers, has great attractions. The limited success which has been attained by trying to bring about such combinations of the two metals through the use of fluxes in welding, has led to the general adoption of the opinion that an effective union of the two metals is impracticable, or to the view that if practicable it would have but limited commercial value. Such opinions are, I think, premature and erroneous, and having gained some knowledge of the character and value of the "Wheeler process" for welding iron and steel without the use of fluxes, I submit the following observations and opinions of the matter for your information, with the hope of eliciting such a discussion of the subject as it may require. The principle of the invention is to bring the two metals simultaneously to a welding heat in one pile, and then to manipulate it.